Optimizing Zakat Management in Improving Community Welfare - Maulana, Aldrian Maulana; Adli, Adlin Ramadhan (Alhamdulillah : Jurnal Agama Islam, 2024)
Optimizing zakat management plays an important role in improving people's welfare and reducing social inequality. This study aims to analyze how efficient zakat management can have a positive impact on empowering the community's economy, especially mustahik (zakat recipients). By utilizing technology in collecting and distributing zakat, as well as paying attention to transparency and accountability, zakat funds can be distributed more effectively and precisely. In addition, empowering mustahik through skills training and business capital assistance has been proven to provide positive results in increasing their economic independence. Collaboration between zakat institutions, the government, and the private sector is key to creating a sustainable zakat distribution system. Although there are still challenges in scalability and infrastructure, optimizing zakat management has the potential to create a more just and prosperous society.